Physical Exercise Program for Osteoporosis in the Elderly: Literature Review - Yoshanda Krisna Paddiansyah; Zakiyatun Nisa; Elsafani Faddiasya (PT FORMOSA CENDEKIA GLOBAL, 2023)
Low bone mass and damage to the microarchitecture of bone tissue are two characteristics of osteoporosis, a systemic bone disease that can raise the risk of fractures. At every stage of life, increasing physical activity positively affects bone health, whereas reducing physical activity can cause bone loss. The purpose of this study was to analyze the effect of a physical exercise program for osteoporosis in the elderly. The technique is a literature review that involves looking for relevant publications using keywords. The inclusion criteria for this study were that the participants in the study were elderly subjects, that the results of the study measured or analyzed the physical exercise program in elderly subjects with osteoporosis, that the study used quasi experiment methods, randomized controlled trials, and cross sectional, that the year of publication of the study was in the time period of 2013–2022, and that the research was conducted in both Indonesian and English. The review's findings indicate that there are six papers that examine physical exercise programs for the elderly, including weight-bearing exercises, balance training, resistance training, and high-intensity resistance and impact training. These exercises can all be performed and have a favorable effect on the elderly. Even if there is no evidence to support the existence of dangers such fractures in physical training programs, it is nevertheless necessary to provide assistance in order to decrease risks.